Analisis Pemetaan Bibliometrik Komputational Publikasi Pada “Ergonomics”, “Human Factor” dan “Occupational Health” dengan Menggunakan VOSviewer - Ario Wicaksono; Indri Hapsari Susilowati; Afifah Mu'minah (Institut Teknologi Adhi Tama Surabaya, 2026)
Ergonomics, Human Factor, and Occupational Health are crucial interrelated disciplines for optimizing human interaction within work systems. Bibliometric analysis offers a quantitative approach to map the development and intellectual structure of these fields. This study aims to conduct a computational bibliometric mapping analysis of scientific publications related to